MAKNA KEMATIAN DALAM LIRIK LAGU ANAK “シャボン玉” (SHABON DAMA) KARYA NOGUCHI UJOU SEBUAH KAJIAN STRUKTURAL DAN SEMIOTIK - Agus Naryoso; Rukti Rumekar; Mj Rizqon Hasani (KIRYOKU, 2023)
This undergraudate thesis examines about the grief meaning of the lyric in Shabon Dama, so the data that used in this research is the lyric of the children song "シ ャ ボ ン 玉" Shabon Dama. The purpose of this study was to determine the meaning that contained in the lyrics of the song. Some stages was done in the analysis by the authors is the collection of library data is analyzed by using the theory of the structure of the poem to find the building blocks of the structure of the physical and mental in the song lyrics Shabon Dama, so after knowing the elements builder, it can helps the writer to know the meaning contained in the song using semiotic theory Riffaterre covering their undirect expression in the poetry, semiotic reading, and determined the matrix and as the supporting theory, the author used the theory of the grief meaning to prove that death is the background, the essence and spirit of the creation of the song. The results of this study are the lyrics of Shabon Dama is not just a children's song alone, but an irony on the lives of people in developed countries who seek to restrict the rights of future generations to live by killing the right to life of children in a modern way. And death is the basis, the main idea, and the idea of the author of the song in creating the lyrics of the song. Imagination of death is a reflection of personal experience that the author of the lyrics feel and see for yourself.